Life-threatening acute acalculous cholecystitis in a patient with renal cell carcinoma treated by sunitinib: a case report - Nakano Kazuhiko (Journal of Medical Case Reports, 2012)
Abstract Introduction Sunitinib, an oral multitargeted tyrosine kinase inhibitor, is widely used in the treatment of renal cell carcinoma and gastrointestinal stromal tumor and has had a variety of adverse events. However, sunitinib-related acute cholecystitis has been reported in only two patients with gastrointestinal stromal tumor and renal cell carcinoma (clear cell subtype). Case presentation A 75-year-old Japanese woman with a right sided abdominal swelling was referred to our hospital. Computed tomography (CT) showed a hypervascular bulky tumor in her right kidney, suggesting right renal cell carcinoma in clinical T4N0M0. Although sunitinib therapy was started as neoadjuvant chemotherapy, during the fourth week of the first cycle, she developed acute acalculous cholecystitis and disseminated intravascular coagulation associated with sunitinib. Sunitinib therapy was discontinued immediately and she recovered after subsequent treatment with antibiotics and gabexate mesilate followed by percutaneous cholecystostomy. Cholecystectomy and right radical nephrectomy were performed and pathological examination showed that her renal tumor was a chromophobe renal cell carcinoma (pT2) with necrosis. Inflammation and ischemia were observed in the gallbladder wall, which was compatible with acute acalculous cholecystitis. There has been no evidence of disease recurrence for more than six months. Conclusion We described the third case of sunitinib-related acute cholecystitis in a patient with chromophobe renal cell carcinoma. Attention is required to sunitinib-related acute cholecystitis which, while uncommon, could be life-threatening.